EFEKTIVITAS KOMBINASI EKSTRAK DAUN JERUK NIPIS DAN PERASAN BUAH JERUK NIPIS (Citrus aurantifolia) TERHADAP MORTALITAS KUTU RAMBUT (Pediculus humanus var capitis) - I Putu Dion Kumara Yadnya; Fahriana Azmi; Ana Andriana; Angelica Vanini Winata Taufiq (Yayasan Nusantara Hasana Berdikari, 2023)
Diseases that tend to occur in tropical climates such as Indonesia are generally infectious diseases, one of which is pediculosis capitis. Risk factors Pediculosis capitis mainly affects young children and women and quickly spreads in a crowded living environment and conditions of poor personal hygiene. The increase in Pediculosis capitis infestations in various countries is due to resistance to the use of synthetic pediculosides. One plant that has potential as a natural insecticide is lime (Citrus aurantifolia). Lime contains saponins, flavonoids, and limonoida compounds. The objective of this study is to determine the effectiveness of a combination of lime leaf extract and lime juice as the most effective natural insecticide for head lice. The method used in this study was true experiment with the design of the Post test with the Control Group (Posttest Only Control Group Design) and Completely Randomized Design (CRD) with 5 treatment groups combination of lime leaf extract and lime juice in a ratio of 1:0, 1:3, 1:1, 3:1, dan 0:1. Results of statistical tests obtained were 0.000 (p <0.05) meaning that there was an effectiveness of the combination of lime leaf extract and lime juice (Citrus aurantifolia) on the mortality of head lice (Pediculus humanus var capitis). The combination of lime leaf extract and lime juice (Citrus aurantifolia) is effective against head lice (Pediculus humanus var capitis) mortality. The most effective combination concentration was 25% lime leaves with 75% lime fruit, 100% lime leaf and 100% lime fruit concentration resulting in 100% head lice mortality 2 hours after the intervention.